Mapping Principal’s Competency of Secondary School - Mika Nusa Putri; Muhammad Kristiawan; Rohana Rohana (INTERNATIONAL JOURNAL OF EDUCATIONAL REVIEW, 2020)
This research aimed at describing the competencies of the Principal in State Secondary school in Banyuasin Regency, it can be mapped the right program given to optimize it. This study was mixed method. The results obtained the competencies of principals in State Secondary schools Banyuasin Regency have moderate managerial competency; entrepreneurship competencies are mostly included in the medium criteria; Supervision competencies in the medium category. Overall, most of the principals have good competency.